AB0425 Plasma vitamin D levels in relation to insulin resistance and risk of metabolic syndrome in rheumatoid arthritis patients. (23rd January 2014) - Seriolo, B.; Paolino, S.; Botticella, G.; Casabella, A.; Molfetta, L.; Sulli, A.; Meroni, M.; Cutolo, M.
Abstract : Background: It has been suggest a link between circulating levels of 25 hydroxyvitamin D [25(OH)D] and metabolic risk factors. It is know that metabolic syndrome (MetS) is strongly predictive of cardiovascular disease(CVD) and in rheumatoid arthritisRA there is an increased risk for CVD due to atherosclerosis resulting from systemic inflammation, medications and insulin resistance. Objectives: The aim of this study is to look at the relations from 25(OH)D levels and the risk factors of MetS and the influence of 25(OH)D levels on insulin resistance Methods: Fiftyfive RA patients (treated with a stable dose of Methotrexate and free of glucocorticoids theraphy from at least three months) were enrolled [mean age 52.3±5.4 years; median disease duration 75±28 months) after informed consent and Ethical Committee approval. Forthy percent of them were positive for the IgM Rheumatoid Factor (>20 IU/ml); 56% were positive for the anti CCP (12.5-20 U/ml]: 29 age- matched subject served as controls. All the patients fulfilled the ACR criteria for the diagnosis of RA and MetS. The Homoeostasis Model Assessment (HOMA) index was used to measure insulin resistance and the Quantitative Insulin Sensitivity Check Index (QUICKI) to measure insulin sensitivity. 25(OH)D was assayed by radioimmunoassay (DiaSorin). Vitamin D levels were classified as normal (>30 ng/ml), insufficient (<30, >10 ng/ml) or deficient (<10 ng/ml). Peripheral blood was collected after a 12 h fasting period. Subjects were classified as MetS positive according to the Adult Treatment Panel III Criteria (1) whenever at least three out of five of the following risk factors were present: increased waist circumference (WC) <102 cm in men and <88 cm in women, elevated serum triglycerides >150 mg/dL, reduced serum high density lipoprotein (HDL-cholesterol) <50 mg/dL in men and 50 mg/dL in womenfasting plasma glucose (FGP) >109 mg/dL, elevated systolic blood pressure (SBP) >130 mmHg and/or diastolic blood pressure (DBP) >85 mmHg. Results: The mean levels of 25(OH)D in RA patients were found significantly lower compared with the control group (74.2±30.9 ng/ml vs 96.8±39.3 ng/ml; p<0.001). 25(OH)D levels in RA patients were inversely correlated with HOMA (p=0.02), Triglycerides (p=0.03), Systolic Blood pressure (p=0.02), HDL-cholesterol (p=0.005), and positively correlated with QUICKI (p=0.02) and Insulin serum levels (p=0.003). However, no relationship was observed between 25(OH)D levels and BMI or Waist circumference. Conclusions: We observed a significant relationship between low levels of 25(OH)D and several metabolic risk factors for MetS in RA patients. Further research is need to elucidate possible relationship between 25(OH)D and the development of MetS. References: National Cholesterol Education Program (NCEP) Circulation 2002;106:3143-3421 Disclosure of Interest: None Declared